Simulation and Impact Analysis of Flooding Caused by the Break of a Concrete-face Rockfill Dam - ZHAN Mingqiang; GUO Yurong; YANG Yanlong; CHEN Bo (Renmin Zhujiang)
Simulation and impact analysis of flooding caused by the break of water reservoir dams is a research priority in the field of prevention and mitigation of disasters surrounding water conservancy projects.To study the scope of submergence and the influencing degree in the downstream areas caused by the break of a concrete-face rockfill dam,by analyzing the characteristics of the concrete-face rockfill dam break,this paper built a one-dimensional unsteady hydrodynamic model of the area from the concrete-face rockfill dam to the hydroelectric power plant reservoir in the downstream.Then,with an actual concrete-face rockfill dam project as a research case,the flood flow distribution under various failure modes of the selected dam case was simulated.The peak flow rate,highest flood level,and the corresponding emergence time of typical sections along the watercourse under the dam were obtained.The results show that the dam-break duration,the final size of the breach,and the water level in front of the dam before the break are the three major factors influencing the simulation calculations with this hydrodynamic model.Shorter duration of dam break,a larger final size of the breach,and a higher water level in front of the dam before the break will lead to a larger peak flow at the dam site.Also,in various dam-break conditions,a large proportion of the major villages and towns on both sides of the downstream flow are expected to be completely submerged.These findings may offer reliable scientific references for the formulation of emergency response and rescue protocols as well as disaster severity evaluation associated with flooding caused by the break of presently active concrete-face rockfill dams.